Alginate gelling process: Use of bivalent ions rich microspheres. Issue 6 (8th March 2017) - Vicini, Silvia; Mauri, Marco; Wichert, Joanna; Castellano, Maila
Abstract : A new approach for obtaining a controlled gelling process of sodium alginate, based on the use of bivalent ions rich alginate microbeads added as crosslinkers, is presented. Normally, calcium ions are used in the gelation of alginate solutions. In this article, alginate microspheres, obtained by electrospray, and enriched with different bivalent ions (Ca 2+, Ba 2+, and Mg 2+ ) are described. Because of the solvent/non‐solvent system, it is possible to use also Mg 2+ as a crosslinker for alginate, despite the fact that it had long been regarded as a nongelling bivalent ion. The morphology and the ions content of the microspheres are evaluated. Gels are characterized according to type and amount of the ions added to the alginate solution, using rheological measurements to assess the variation in the storage modulus ( G ′) and loss modulus ( G ″). The gel point is then detected using magnesium ions. The new approach guarantees a working system that could be easily applied in different fields. POLYM. ENG. SCI., 57:531–536, 2017. © 2017 Society of Plastics Engineers